Analysis of the microbial spectrum of urinary tract infections and antibiotic resistance of UPEC in Central Inner Mongolia, China - Zhang, Jingru; Wen, Shengyuan; Chen, Liqing; Qin, Jianxiong; Liu, Ziling (Frontiers in Microbiology, 2025)
Urinary Tract Infections (UTIs) remain a significant global health concern, with the pathogen spectrum and antibiotic resistance patterns critically influencing clinical management. This study aimed to analyze the microbial profile of UTIs from 2022 to 2024, focusing on Escherichia coli (E. coli), the predominant pathogen, by evaluating its antibiotic resistance phenotypes, biofilm formation capability, and mutations in GyrA, ParC and Plasmid-Mediated Quinolone Resistance (PMQR) genes prevalence. Midstream urine samples from UTI patients were collected and analyzed for microbial identification. E. coli isolates were tested for antibiotic susceptibility, particularly to levofloxacin, the most frequently used antibiotic in our hospital. Biofilm formation was assessed, and mutations in GyrA, ParC and PMQR genes were sequenced to determine resistance mechanisms.The pathogen spectrum revealed that Enterobacteriaceae were the most prevalent (44.42%), with E. coli being the dominant species. Over 70% of E. coli isolates exhibited resistance to levofloxacin, and 58.97% (46/78) demonstrated biofilm-forming ability. Among levofloxacin-resistant strains, 75.64% (59/78) showed high-level resistance (MIC ≥ 8μg/mL). The most common mutations in GyrA were Ser83Leu (89.74%) and Asp87Asn (71.79%), while Ser80Ile (74.36%) was predominant in ParC. PMQR genes were detected in 17.95% (14/78) of isolates. The elevated prevalence of quinolone-resistant E. coli in urinary tract infections within this region, combined with intricate resistance gene mutations and generally strong biofilm-forming capabilities, underscores the critical necessity for rational antibiotic stewardship.